Belacan Tale - Despite its pungent aroma, sambal belacan is hard to resist, as two members of a research team discover - The Star, Grace Chen (2008)
How ironic that the much-loved sambal belacan, a zesty sauce of roasted fermented shrimp blocks pounded with fresh chillies, shallots and asam jawa or some lime juice, should also emit such an awful pong